2020
DOI: 10.18295/squmj.2020.20.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Needle Stick and Sharp Injuries Among Healthcare Workers: A retrospective six-year study

Abstract: Objectives: This study aimed to examine the proportion of needle stick and sharp injuries (NSSIs) among healthcare workers at King Hussein Medical Center (KHMC), Amman, Jordan. Methods: All NSSI reports referred from departments at KHMC to the Preventive Medicine Department between 2013–2018 were retrospectively reviewed. Proportion of NSSIs were calculated and stratified according to age, gender, job title, place and site of injury and the procedure/task during which the injury occurred. Results: There were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 24 publications
7
42
1
2
Order By: Relevance
“…NSI-related risk factors have not yet been properly identified in Iran. Studies have identified factors such as excessive and unnecessary injections, poor personnel training, female gender, high workloads, and excessive fatigue especially at nighttime as the most important causes of NSI [ 7 , 12 17 ]. Moreover, a systematic review found age, level of education, number of shifts per month, and history of training courses for individuals as factors influencing NSI.…”
Section: Introductionmentioning
confidence: 99%
“…NSI-related risk factors have not yet been properly identified in Iran. Studies have identified factors such as excessive and unnecessary injections, poor personnel training, female gender, high workloads, and excessive fatigue especially at nighttime as the most important causes of NSI [ 7 , 12 17 ]. Moreover, a systematic review found age, level of education, number of shifts per month, and history of training courses for individuals as factors influencing NSI.…”
Section: Introductionmentioning
confidence: 99%
“…This might be explained by the higher number of patients senior-level students encounter in the clinical training, as well as the more complex clinical cases that require the use of sharp instruments and needles more frequently, especially in oral surgeries. Generally, around 60% and 40% of the students had experienced needle and sharps injuries, respectively, which has been also documented in other developing countries such as Yemen, Iran, and Nigeria [ 37 , 38 , 41 , 42 ]. This highlights the critical need for post-exposure risk management among dental students.…”
Section: Discussionmentioning
confidence: 75%
“…Similar trends have been observed among dental students in other countries [ 38 , 39 ]. This may be due to the tendency of female students to recall such incidences more accurately than male students [ 40 , 41 ]. Otherwise, female students might be exposed to more injury incidences during clinical practice [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common modes of transmission is needle stick and sharp injuries (NSSIs) 2 . NSSIs are common, yet these are considered preventable occupational hazards among HCWs because of the current availability of precaution guidelines and increased awareness 3 . The World Health Organization (WHO) estimates that approximately two million NSSI cases are reported annually; however, this number could be underestimated as many cases of NSSIs are not reported, especially in developing countries 3,4 .…”
Section: Introductionmentioning
confidence: 99%